2010
DOI: 10.5336/medsci.2008-9639
|View full text |Cite
|
Sign up to set email alerts
|

The Viewpoints of Law and Medical Faculty Students on Organ Donation and Transplantation: A Study in Turkey

Abstract: ABS TRACT Ob jec ti ve: This study is car ri ed out in or der to find out the know led ge, at ti tu des, beha vi ors, an xi e ti es and re ser va ti ons of 1st and 3rd ye ar stu dents in the Fa culty of Me di ci ne, Es ki sehir Os man ga zi Uni ver sity and 1st ye ar stu dents in the Fa culty of Law Ana do lu Uni ver sity abo ut or gan do na ti on and trans plan ta ti on. Ma te ri al and Met hods: Par ti ci pants res pon ded to the qu es tions in the qu es ti on na i re re la ted to the or gan do na ti on and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…A study from Spain also described discussing OD with friends and family as one of the reasons underlying the willingness to donate organs 21 . Finally, a study from Turkey concluded that negative attitudes toward OD on the part of the family adversely affected students' attitudes toward donation 22 . An environment and family favorably disposed to OD can increase the willingness to donate organs.…”
Section: Discussionmentioning
confidence: 99%
“…A study from Spain also described discussing OD with friends and family as one of the reasons underlying the willingness to donate organs 21 . Finally, a study from Turkey concluded that negative attitudes toward OD on the part of the family adversely affected students' attitudes toward donation 22 . An environment and family favorably disposed to OD can increase the willingness to donate organs.…”
Section: Discussionmentioning
confidence: 99%